Efectos de pulpa de camote (toquecita) y dos tipos de hidrocoloides en la composición y calidad de una salsa de ají con maracuyá - Cevallos Domínguez, Jefferson Antonio (2022)
The purpose of investigation was to evaluate the effects of sweet potato pulp (Toquecita) and two hydrocolloids (Xanthan and Guar gums) on the composition and quality of a chili sauce with passion fruit were evaluated. An AxB bifactorial design was used in CRD (Complete Random Design), with three repetitions, two factors were studied factor A. Percentage of Toquecita sweet potato pulp (a1: 10%, a2: 15% and a3: 20%); and, Factor B. Percentage of Hydrocolloids (b1: Guar Gum 0.5%; b2: Xanthan Gum 0.5%). Parameters were evaluated: Acceptability of the product (smell, color, flavor and texture), by Sequential Monadic Presentation to 80 untrained panelists; and physicochemical (pH, °Brix, Consistency and Sodium Chloride). The results showed that Sodium Chloride did not present a significant difference p>0.05; while for the variables of pH, °Brix and Consistency they did not accomplish the assumptions of the ANOVA, presenting statistical significance p<0.05; in this way, the best treatments were for pH T2, °Brix treatments T1 and T3; and for the Consistency variable, they were T3 and T5. In sensory evaluation, the best treatments were T1, T3 and T5 according to the ratings obtained by the not trained panelist as sensorial evaluators.